Unveiling the Transformative Effects of Forest Restoration on the Soil Chemistry and Biology of Sandy Soils in Southern Nyírség, Hungary - István Attila Kocsis; Magdolna Tállai; Ágnes Zsuposné Oláh; Zoltán László; Béla Mokos; Ida Kincses; Evelin Kármen Juhász; Daniel A. Lowy; Zsolt Sándor (Agriculture)
Protecting humankind’s natural resources and soils, including forestry, represents a top priority in agriculture. Addressing climate change should prioritize preserving and enhancing organic carbon, specifically humus, in soils. In this paper, we examine the impact of soil preparation on soil humus and microbial life during the reforestation of Southern Nyírség, Hungary. We determined soil plasticity, pH in distilled water solution, the quantity and quality of humus content, the total number of bacteria and microbial fungi, as well as CO2 production. In addition to stump removal and plowing, the wealthiest layer of organic matter was detached from the surface. A significant decrease in humus content (HU%) was observed at the five experimental sites (loss of 19.20–40.14 HU% at 0–30 cm depth). Soil organic matter is concentrated in the stump depositions. According to the results, the quantity of humus content is strongly correlated with the measured parameters of soil life, specifically with the number of microbial fungi (r = 0.806 **) and the total number of bacteria (r = 0.648 **). Another correlation (r = 0.607 **) was assessed between the humus content and CO2 production. This study helps to understand the importance of the no-tillage methods used in reforestation.